FLAIR-hyperintense lesions in anti-MOG-associated encephalitis with seizures overlaying anti-N-methyl-D-aspartate receptor encephalitis: a case report and literature review - Yang, Jia-Xin; Yang, Miao-Miao; Han, Yu-Juan; Gao, Cai-Hong; Cao, Jie (Frontiers in Immunology, 2023)
Background FLAIR-hyperintense lesions in anti-MOG-associated encephalitis with seizures (FLAMES) has been identified increasingly frequently in recent years. However, this rare MOG antibody disease may coexist with anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARe), in an overlap syndrome with unknown clinical features and prognosis. Methods We report a new case of this overlap syndrome and present a systematic review of similar cases in the literature to provide information on the clinical presentation, MRI features, EGG abnormalities, treatment, and prognosis of patients with this rare syndrome. Results A total of 12 patients were analyzed in the study. The most common clinical manifestations of FLAMES overlaid with anti-NMDARe were epilepsy (12/12), headache (11/12), and fever (10/12). Increases in intracranial pressure (median: 262.5 mmH2O, range: 150–380 mmH2O), cerebrospinal fluid (CSF) leukocyte count (median: 128×106/L, range: 1-610×106/L), and protein level (median: 0.48 g/L) were also observed. The median CSF anti-NMDAR antibody titer was 1:10 (1:1–1:32), while the median serum MOG antibody titer was 1:32 (1:10–1:1024). Seven cases exhibited unilateral cortical FLAIR hyperintensity, and five cases (42%) had bilateral cortical FLAIR hyperintensity, including four cases involving the bilateral medial frontal lobes. Of the 12 patients, five showed lesions at other sites (e.g., the brainstem, corpus callosum, or frontal orbital gyrus) before or after the development of cortical encephalitis. EEG showed slow waves in four cases, spike–slow waves in two cases, an epileptiform pattern in one case, and normal waves in two cases. The median number of relapses was two. Over a mean follow-up period of 18.5 months, only one patient experienced residual visual impairment, while the remaining 11 patients had good prognoses. Conclusion FLAMES alone is difficult to distinguish from overlap syndrome based on clinical features. However, FLAMES with bilateral medial frontal lobe involvement suggests the presence of the overlap syndrome.